Diversity of antibiotic-producing Actinomycetes in mangrove forest of Torosiaje, Gorontalo, Indonesia - YULIANA RETNOWATI; LANGKAH SEMBIRING; SUKARTI MOELJOPAWIRO; TJUT SUGANDAWATY DJOHAN; ENDANG SUTARININGSIH SOETARTO (Biodiversitas Journal of Biological Diversity, 2017)
Retnowati Y, Sembiring L, Moeljopawiro S, Djohan TS, Soetarto ES. 2017. Diversity of antibiotic-producing actinomycetes in mangrove forest of Torosiaje, Gorontalo, Indonesia. Biodiversitas 18: 1453-1461. Actinomycetes for antibiotic production have been studied at various extreme environments. Mangrove forest of Torosiaje in Gorontalo Province, Indonesia has unique geomorphological conditions where the forest is surrounded by karst ecosystem consisting of fringe and overwash types. Therefore, the objective of this study was to analyze the distribution and diversity of antibiotic-producing Actinomycetes in various rhizosphere including different locations and mangrove species. Samples of rhizosphere soil were collected in the depth of 0-10 cm, which was then subjected to detailed physicochemical analysis. Actinomycetes were collected through heating pre-treatment (60oC for 15 min) followed by culturing in the Starch Casein Agar medium supplemented with cycloheximide and nystatin. The screening process of antibiotic-producing Actinomycetes was based on Agar block method against pathogenic microorganisms. Grouping of Actinomycetes was determined by ARDRA fingerprinting analysis. The diversity of Actinomycetes was analyzed based on sequencing of 16S rDNA. The results showed that the distribution of Actinomycetes was found in overwash type, middle zone and upper zone of fringe type including rhizosphere of 7 species of mangrove. The highest population of Actinomycetes was found in rhizosphere of R. mucronata at the overwash type, and the lowest one found in rhizosphere of R. apiculata at the middle zone of fringe type. A total of 77 isolates amongst 167 isolate collection showed antibacterial activities. Forty seven representatives from 77 antibacterial-activities isolates were selected using ARDRA for partial characterization according to their phylogenetic diversity. Sequencing and analysis of 16S rDNA from selectedrepresentative isolates displayed the presence of members associated with Actinomycetes genera such as Streptomyces, Amycolatopsis, Saccharomonospora, and Nocardiopsis. The member of genus Streptomyces such as Streptomyces qinglanensis and Streptomyces champavatii were distributed across locations. Genus Saccharomonospora and Nocardiopsis were mostly found at the overwash type, while Amycolatopsis was found at the upper zone of fringe type.